Comparative mitogenomes reveal diverse and novel gene rearrangements in the genus Meteorus (Hymenoptera: Braconidae) - Shu, Xiaohan; Yuan, Ruizhong; Xia, Zhilin; Gao, Gui; Yang, Lei; Sun, Zhirong; Mu, Qing; Tang, Pu; Chen, Xuexin (Frontiers in Genetics, 2023)
Meteorus Haliday, 1835 is a cosmopolitan genus within Braconidae (Hymenoptera). They are koinobiont endoparasitoids of Coleoptera or Lepidoptera larvae. Only one mitogenome of this group was available. Here, we sequenced and annotated three mitogenomes of Meteorus species, and found that the tRNA gene rearrangements in these mitogenomes were rich and diverse. Compared with the ancestral organization, only seven tRNAs (trnW, trnY, trnL2, trnH, trnT, trnP and trnV) were conserved and trnG had its own unique location in the four mitogenomes. This dramatic tRNA rearrangement was not observed in mitogenomes of other insect groups before. In addition, the tRNA cluster (trnA-trnR-trnN-trnS1-trnE-trnF) between nad3 and nad5 was rearranged into two patterns, i.e., trnE-trnA-trnR-trnN-trnS1 and trnA-trnR-trnS1-trnE-trnF-trnN. The phylogenetic results showed that the Meteorus species formed a clade within the subfamily Euphorinae, and were close to Zele. In the Meteorus, two clades were reconstructed: M. sp. USNM and M. pulchricornis forming a clade while the remaining two species forming another clade. This phylogenetic relationship also matched the tRNA rearrangement patterns. Our results provided new insight into tRNA rearrangements of the mitochondrial genome at genus/species levels in insects.